Pengaruh Budaya Organisasi dan Iklim Komunikasi Terhadap Kinerja Karyawan dengan Knowledge Sharing Sebagai Variabel Mediasi Pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Medan - Hasibuan Nurcahaya; Bagus Handoko; Alvin Fahlevi (Cattleya Darmaya Fortuna, 2023)
This study aims to determine the influence of organizational culture and communication climate on knowledge sharing partially. To determine the effect of organizational culture, communication climate and knowledge sharing on employee performance partially. To determine the influence of organizational culture and communication climate on employee performance through knowledge sharing at the Medan City Regional Tax and Retribution Management Agency. The total population in this study amounted to 249 people and 153 people were used as samples using the Slovin formula. The analysis technique used is path analysis. The results show that organizational culture has no effect on employee performance, communication climate has no effect on employee performance, organizational culture has a positive and significant effect on knowledge sharing, communication climate has no effect on knowledge sharing, knowledge sharing has a positive and significant effect on employee performance, knowledge sharing mediates the influence of organizational culture on employee performance and knowledge sharing does not mediate the effect of communication climate on employee performance.